Nuclear decommissioning profile: Switzerland - Rebekka Bärenbold (University of Basel, Center of Business and Economics (WWZ), 2023)
This report provides an overview of the legal framework and regulation for the decommissioning of NPPs in Switzerland, as well as give an indication on current cost estimates and their accuracy. Additionally, it shows the current progress of the decommissioning process.
Keywords: 330; Kernkraftwerk; Nukleare Entsorgung; Altlastensanierung; Kernenergiepolitik; Regulierung; Finanzierung; Schweiz